2-[(5-Chloro-2-hydroxybenzylidene)amino]-3′,6′-bis(diethylamino)spiro[isoindoline-1,9′-xanthen]-3-one - Xu, Zhi-hong (International Union of Crystallography, 2010)
The title compound, C(35)H(35)ClN(4)O(3), resulted from a spirolactam ring closure of rhodamine B dye. The xanthene ring system is approximately planar [r.m.s. deviation = 0.050 (9) Å for the xanthene ring]. The dihedral angles formed by the spirolactam and 5-chloro-2-hydroxybenzene rings with the xanthene ring system are 87.9 (7) and 79.1 (7)°, respectively.